DEVELOPMENT OF MILITARY PATRIOTIC TRAINING IN STUDENTS OF UPPER EDUCATION ESTABLISHMENTS (Archive of Conferences, 2021)
This article discusses development of military patriotic training in students in higher education. It is emphasized that educating students in the spirit of patriotism is a high priority